2003
DOI: 10.1021/jo026783j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Highly Regioselective VO(acac)2/TBHP Mediated Oxidation of o-Alkenyl Phenols to o-Hydroxybenzyl Ketones

Abstract: A novel mild methodology for the preparation of o-hydroxybenzyl ketones is described starting from o-alkenyl phenols and based on the VO(acac)(2)/TBHP (2 mol %/1.2 equiv) system. VO(acac)(2) first catalyzes the epoxidation of o-alkenyl phenols and then the rearrangement of the epoxyphenols to ketones via the selective benzylic C-O cleavage and 1,2 hydride migration. The protocol has also been applied to set up a useful and easy one-pot conversion of o-alkenyl phenols to benzo[b]furans by means of the sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…In Path A, under a basic environment, the intramolecular attack of the phenoxide oxygen atom occurs to form a dihydrobenzofuran intermediate, followed by the elimination of nitric oxide and water. In contrast, Path B involves a conventional Nef reaction: in the presence of an acid, the nitroate forms ketone 5a , after which the phenol attacks the carbonyl group to complete the cyclization,10e and the subsequent dehydration of the dihydrobenzofuran furnishes the benzofuran 6a . To investigate the possibility of Path A, we examined the reaction with nitroalkane 4a in an aqueous NaOH solution, followed by treatment with an aqueous NH 4 Cl solution.…”
Section: Resultsmentioning
confidence: 99%
“…In Path A, under a basic environment, the intramolecular attack of the phenoxide oxygen atom occurs to form a dihydrobenzofuran intermediate, followed by the elimination of nitric oxide and water. In contrast, Path B involves a conventional Nef reaction: in the presence of an acid, the nitroate forms ketone 5a , after which the phenol attacks the carbonyl group to complete the cyclization,10e and the subsequent dehydration of the dihydrobenzofuran furnishes the benzofuran 6a . To investigate the possibility of Path A, we examined the reaction with nitroalkane 4a in an aqueous NaOH solution, followed by treatment with an aqueous NH 4 Cl solution.…”
Section: Resultsmentioning
confidence: 99%
“…The reactivity of complexes 6-M towards both paraoxon-ethyl and profenofos nerve simulants under analogous reaction conditions also proved successful; cleavage of P-OAr bond was identified by 31 P NMR spectroscopy after 20 h at 80°C (Scheme 6b). A proposed mechanism is outlined in Scheme 8, in which the nucleophilic carbene attacks the phosphorus centre, leading to M-OAr bond formation then P-OAr bond cleavage.…”
Section: Destruction By Complexes Of Tethered-nhcsmentioning
confidence: 93%
“…22 Oxidative CWA destruction pathways can also be considered in combination with right choice of metal centre. Many coinage metal NHC complexes made for medicinal applications display very high water stability, 23 while homogeneous catalysts based on Pd and V show both a high stability towards oxidation [24][25][26][27][28] and great efficacy as oxidation catalysts, [29][30][31] in particular vanadium doped silica has been previously shown to be effective for the oxidation of CEES. The redox couple of VO 2 + /VO 2+ (vanadyl) complexes is +1.00 V, 32 and it has been demonstrated that the complex VOCl 3 (IMes) is air-stable.…”
Section: Introductionmentioning
confidence: 99%
“…Activation by the phenolic OH of the epoxidation of 32 provides 11 A. The high instability of such a compound [83] brings on spontaneous ring opening leading to 30 and 31 R . However, the strong acceleration of the palladium-catalyzed reaction of 32 (Equation (19)) indicates some participation of Pd(OCOCF 3 ) 2 /L H in the process [80].…”
Section: Allylphenols Oxidationmentioning
confidence: 99%